Siblings Gender: Fulfillment of Rights, Role Allocation, and Responsibilies of Children in The Family - Aminuddin, Ahsani Taqwim; Fathonah Nuraisyiah, Siti; Wardani, Yasmin Sarah; Azzahra, Latisa (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
Gender equality within the family has become an important goal in social development. The modern family is a place where decisions are made collectively, responsibilities are shared fairly, and each family member is respected in their diverse roles. This paper discusses how parents involve both boys and girls in the decision-making process, include them in discussions, provide them with the space to make choices, grant them the right to pursue education, and assign equal or unequal household tasks, a concept known in sociological studies as siblings gender. Using survey methods and in-depth interviews, this study involved 87 respondents who met the criteria required for the research. The results indicate that many respondents feel that their families have implemented gender equality. Both boys and girls feel they are treated well and fairly, and decisions are made by mutual agreement. However, some respondents reported being treated unfairly as they were not allowed to pursue education outside their current city, unlike their brothers who could attend college elsewhere. Other positive impacts of gender equality within the family include improved family welfare, harmony in family relationships, and the formation of positive behavioral patterns among family members.